2006
DOI: 10.1525/si.2006.29.4.507
|View full text |Cite
|
Sign up to set email alerts
|

Role Strain, Emotion Management, and Burnout: Homeschooling Mothers' Adjustment to the Teacher Role

Abstract: Drawing from three years of field research with a homeschooling support group in the Pacific Northwest, I present the emotional stages mothers passed through as they tried to integrate the teacher role into their busy lives. In most cases, mothers found teaching more demanding than they had expected, straining their other roles as mothers and homemakers, as well as causing emotional burnout. To manage their insecurity, anxiety, and stress, mothers employed a variety of emotion management techniques. Mothers wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 57 publications
3
67
1
Order By: Relevance
“…The girls' misbehaviors reflected their supposed incompetence as workers, and they took disobedience personally. Their accountability for so many girls led to role overload that was exhausting (Lois 2006;Thoits 1985). Thus, staff mitigated their own negative emotions and, ultimately, emotional burnout, by socializing girls in deferential emotional capital.…”
Section: Discussionmentioning
confidence: 99%
“…The girls' misbehaviors reflected their supposed incompetence as workers, and they took disobedience personally. Their accountability for so many girls led to role overload that was exhausting (Lois 2006;Thoits 1985). Thus, staff mitigated their own negative emotions and, ultimately, emotional burnout, by socializing girls in deferential emotional capital.…”
Section: Discussionmentioning
confidence: 99%
“…Terms & homeschooling undermines civic values and the socialization goals of public education (see Carper 2000;Hill 2000;Kunzman 2009;Lubienski 2000;Reich 2002). Recently, there has been a welcome sociological focus on the role of mothers in homeschooling households, namely, studies on mothers' role strain and time management strategies (Lois 2013(Lois , 2010(Lois , 2006). Yet, there remains an inexplicable lack of sociological focus on the social role of fathers in homeschooling families.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…'' Lois' subjects also revealed that although fathers did contribute intermittently to child care, their contribution was not enough to give the mothers the necessary ''me-time'' away from their children, and so ''mothers resorted to other methods of creating personal time that did not depend on their physical separation from the children'' (Lois 2013:121). Lois (2006) explains how mother-teachers potentially experience two types of burnout, from both in-home emotion work that comes with dealing with familial relationships, and Hochschild's emotion labor, wherein workers must manipulate their own emotions to give the perception of positivity (see Wharton 2009). Lois (2006) finds that role strain is exacerbated for mother-teachers whose work and private lives are so intertwined.…”
Section: The Homeschooling Mothermentioning
confidence: 99%
See 2 more Smart Citations